2019
DOI: 10.5897/ajps2019.1923
|View full text |Cite
|
Sign up to set email alerts
|

In vitro seed germination and seedling growth of the orchid Dendrobium primulinum Lindl.

Abstract: Dendrobium primulinum Lindl. (D. Primulinum L.) is one of the important epiphytic orchid species for horticultural and commercial use. It is listed as a rare and critically endangered species of orchid. The present study is intended to conserve the orchid species through the micropropagation technique. The in vitro seed germination and seedling growth was carried out by taking a mature pod of D. Primulinum L. in Murashige and Skoog (MS) media, and the MS media supplemented with a varied concentration (0.5, 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…En P. dubium, la máxima frecuencia de germinación y altura promedio de las plántulas se obtuvo en las semillas germinadas en medio MS½ en presencia de 0,1 mg/l de BAP; mientras que en E. contortisiliquum los valores máximos de germinación y altura de plántulas se observó en medio MS libre de BAP. En P. dubium pudimos observar un efecto positivo de la presencia del BAP en el medio de germinación, tanto en la capacidad germinativa, como en el desarrollo posterior de las plántulas in vitro, en concordancia a lo demostrado por Asif et al (2001); Nikolić et al (2006); Akram & Aftab (2015); y Hira & Bijaya (2019). Sin embargo, en la mayoría de las publicaciones especificas en P. dubium, la germinación in vitro de las semillas se realizó en agar-agua sin macro, micronutrientes, ni RCV (Bassan et al, 2006;Curti, 2011;Flôres et al, 2011;Candido, 2013;Gomes, 2017;Andreolla, 2019), solamente Fruet (2018) menciona el uso de MS½ enriquecido con 30 g/l de sacarosa en la germinación de las semillas de P. dubium; pero ninguno abordó el estudio del efecto del medio nutritivo en la germinación.…”
Section: Discussionunclassified
“…En P. dubium, la máxima frecuencia de germinación y altura promedio de las plántulas se obtuvo en las semillas germinadas en medio MS½ en presencia de 0,1 mg/l de BAP; mientras que en E. contortisiliquum los valores máximos de germinación y altura de plántulas se observó en medio MS libre de BAP. En P. dubium pudimos observar un efecto positivo de la presencia del BAP en el medio de germinación, tanto en la capacidad germinativa, como en el desarrollo posterior de las plántulas in vitro, en concordancia a lo demostrado por Asif et al (2001); Nikolić et al (2006); Akram & Aftab (2015); y Hira & Bijaya (2019). Sin embargo, en la mayoría de las publicaciones especificas en P. dubium, la germinación in vitro de las semillas se realizó en agar-agua sin macro, micronutrientes, ni RCV (Bassan et al, 2006;Curti, 2011;Flôres et al, 2011;Candido, 2013;Gomes, 2017;Andreolla, 2019), solamente Fruet (2018) menciona el uso de MS½ enriquecido con 30 g/l de sacarosa en la germinación de las semillas de P. dubium; pero ninguno abordó el estudio del efecto del medio nutritivo en la germinación.…”
Section: Discussionunclassified
“…Different results were obtained by Mahendran, Muniappan, Ashwini, Muthukumar, and Bai (2013) who reported that increasing BA concentration from 1 to 2 mg L -1 caused a decrease in shoot formation of Cymbidium bicolor. In different orchid species it has been demonstrated that organogenesis and growth are highly favored by the interaction of auxin and cytokinin (Picolotto et al, 2017;Adhikari & Pant, 2019).…”
Section: Effects Of Growth Regulators On Seedling Multiplication and ...mentioning
confidence: 99%
“…PGR are chemical substances that affect the growth and differentiation of plant cells, tissues and organs (Hira and Bijaya, 2019). One method that can be done to increase shoot growth is the addition of cytokinins.…”
Section: Introductionmentioning
confidence: 99%